Secularism and religion - Cipriani, Roberto (2020)
Each religion tends to consolidate itself more and more; it looks for its independence with respect to all form of State as well as with respect to the other religions with which it competes. Indeed, a new conception of laicism, understood like a common space, a public place of coexistence is emerging. And therefore original identities are in crisis, together with consolidated traditions, borders and limits. It has been maintained that the laicism necessarily implies to grant the freedom of consciousness and not only to assure the freedom of consciousness. The question is still more complex when a decreasing priority order between freedom and belief, freedom of knowledge and freedom of critic is established. The recognition of religion is also present in some cases in the fundamental laws of the States, their constitutions, in which the natural diversification between State and Church is emphasized, but interchanges and co-participations are admitted.